Analysis of The Effects of Social Media Marketing (Instagram) and Perceived Price on Purchase Intention - Kezia Audrylia; Putu Adi (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to examine the effects of social media marketing through Instagram and perceived price on purchase intention among prospective consumers of Nomé Macaroll, a food and beverage business offering rice paper-based macaroni products. Design/Methodology/Approach – This study employs an explanatory quantitative research approach. Data were collected through 7-point Likert-scale questionnaires distributed to 120 prospective consumers who represent the target market and have not previously purchased Nomé Macaroll products. The data were analyzed using multiple linear regression with SPSS version 30 to examine the effects of social media marketing and perceived price on purchase intention. Findings – The results indicate that social media marketing through Instagram has a positive and significant effect on purchase intention. Perceived price also has a positive and significant effect on purchase intention. These findings suggest that effective digital promotion and appropriate pricing strategies are important factors in attracting prospective consumers and increasing market acceptance for new food and beverage products. Originality/Value This study provides new insight by examining the combined influence of Instagram marketing and perceived price on purchase intention for a newly introduced rice paper–based product, offering empirical evidence that supports more effective marketing decisions.